2008
DOI: 10.1103/physrevb.78.024417
|View full text |Cite
|
Sign up to set email alerts
|

Current fluctuations and magnetization dynamics symmetry in spin-torque-induced magnetization switching

Abstract: We studied spin-torque-induced magnetization switching with current fluctuations using models and experiment measurements. It was found that the efficiency of accelerating magnetization reversal by noisy current strongly depends on the symmetry of magnetization dynamics. The efficiency of noisy current on accelerating magnetization switching is quite different for a magnetic thin-film element without rotational symmetry and a uniaxial anisotropy magnetic element with rotational symmetry. The study reveals that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…where H s is the spin torque term, (7) I is the current density, p is the spin polarization coefficient, q is the electron charge. In the simplified treatment of the Fokker-Plank equation [10], it is assumed that the magnetic field H and n s are parallel to the anisotropy axis, i.e., H e = (H+H k cosθ) e z and n s = e z where H k = 2K/M s .…”
Section: Simplified Fokker-plank Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…where H s is the spin torque term, (7) I is the current density, p is the spin polarization coefficient, q is the electron charge. In the simplified treatment of the Fokker-Plank equation [10], it is assumed that the magnetic field H and n s are parallel to the anisotropy axis, i.e., H e = (H+H k cosθ) e z and n s = e z where H k = 2K/M s .…”
Section: Simplified Fokker-plank Equationmentioning
confidence: 99%
“…First, the initial position of the magnetic moment is thermally distributed at the time the reversal field or current is applied, causing a variation in switching time. Secondly, during reversal, thermal fluctuation would modify the orbit, [4][5][6][7] causing additional fluctuation for τ s even for identical initial conditions. The dynamics of a macrospinunder spin-torque-driven magnetic reversal has been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…Previously we have studied both the averaged magnetization switching and the switching variations in the nanosecond to second range based upon the stochastic Landau-Lifshitz-Gilbert ͑LLG͒ equation with a phenomenological spin torque term. 6,7 In this paper we investigate the intrinsic spin torqueinduced magnetization switching asymmetry between the high and low resistance states due to asymmetric ballistic spin transport across the magnetic tunneling junction for voltages biased in different directions. In order to explicitly consider spin torque's dependence upon biasing voltage, we expand the previous model to include the microscopic ballistic quantum spin tunneling process.…”
Section: Introductionmentioning
confidence: 99%
“…A symmetric factor that depends upon element anisotropy factors must be considered when scaling the thermal reversal barrier to switching current. [23] studied spin torque current fluctuation effects on spin torque induced magnetization switching. Theoretical and experimental work showed that fluctuating current effects on spin torque switching strongly depends upon magnetization dynamics symmetry.…”
Section: Symmetry Effects On Magnetic Element Stability Under Spin Tomentioning
confidence: 99%